DINAMIKA PONDOK PESANTREN GONTOR DALAM MODERNISASI - Saeful Rahmat (LPPM UNY, 2002)
Abstract We believe that education is a pivotal means of empowering man resources if it is constructed systematically in conjuction with our culture in which consists of elements such as approach, stategy and technique. Pondok pesantren (ponpes) is a traditional education institution which is still admitted by the people and the latter believe that ponpes is able to become an alternative education in modern era which has stigmatic feature of moral decadency. However ponpes continue revitalizing its educational system by time goes such as it is done by Pondok Modern Gontor (PMG). It rises some critical questions that are: (1)what factors do support its success, (2) howdoes it construct its educational system, (3)how does it have relationship with the society, and (4)how success does it reach? I use a new historical method so as to handle historic events not only narrative-descriptively,but also seeks the meaning of them critically. That is why I use multiple-dimension approaches, that is study historic events from multiple point of views by using some method of social sciences. Meanwhile in analyzing data I do with the stages of critical history method namely heuristic, critic resources, interpretation and report.PMG originate from traditional educational system by adding secular subjects in its curriculum. The triumvirate founders of PMG were influenced by M, Abduh’s ideas so that they did teach tasawuf subjects in their modern ponpes. Moreover thay did not teach kitab kuning, trade mark of traditional educational system; although they ordered their students of the last stage to submit the report about the study of kitab kuning. However the existence of PMG is stilladmitted by the Muslim because it has continuities of history, of ideology and of genealogy. The form of pondok continues historically a traditional education institution. Genealogically the triumvirate founders of PMG were still a clerical family of Tegalsari who established ponpes in 1742 and they also continued the ideology school of ahl al-sunnah wa al-jamaah. Keywords:education,traditional, and continue